2011
DOI: 10.1007/s10571-011-9776-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacopa monnieri Extract Offsets Rotenone-Induced Cytotoxicity in Dopaminergic Cells and Oxidative Impairments in Mice Brain

Abstract: Bacopa monnieri (BM), an ayurvedic medicinal herb is widely known for its memory enhancing ability and improvement of brain function. In this study, we tested the hypothesis that BM extract (BME) could offset neurotoxicant-induced oxidative dysfunctions in developing brain in a rotenone (ROT) mouse model. Pretreatment of dopaminergic (N27 cell lines) cells with BME exhibited significant cytoprotective effect as evidenced by the attenuation of ROT-induced oxidative stress and cell death. Further, the neuroprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…A similar positive impact on TTR amyloidogenesis by natural agents with potent antioxidant activities had been previously observed in carvedilol, TUDCA, curcumin, and green tea extracts, which were shown to significantly reduce deposition of amyloid TTR despite their less impressive effect on tetramer stability [45][46][47][48]. Previous studies have reported the neuroprotective effects of B. monnieri in diseases such as Alzheimer's disease [49], Parkinson's disease [37], and neurotoxicant-induced brain dysfunction [50]. Our investigation for the first time provides in vitro evidence for the protective role of BME in modulating transthyretin amyloidogenesis.…”
Section: Discussionsupporting
confidence: 72%
“…A similar positive impact on TTR amyloidogenesis by natural agents with potent antioxidant activities had been previously observed in carvedilol, TUDCA, curcumin, and green tea extracts, which were shown to significantly reduce deposition of amyloid TTR despite their less impressive effect on tetramer stability [45][46][47][48]. Previous studies have reported the neuroprotective effects of B. monnieri in diseases such as Alzheimer's disease [49], Parkinson's disease [37], and neurotoxicant-induced brain dysfunction [50]. Our investigation for the first time provides in vitro evidence for the protective role of BME in modulating transthyretin amyloidogenesis.…”
Section: Discussionsupporting
confidence: 72%
“…Part of its effect may be explained by its protection against oxidative stress and damage, as demonstrated in several studies (e.g. Jyoti and Sharma, ; Hosamani and Muralidhara, ; Saini et al ., ; Shinomol and Muralidhara, ; Shinomol et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our study showed that B[a]P‐induced apoptosis was diminished by BM treatment in HaCaT cells which was supported by the previous study. It showed that BM found to protect rotenone‐induced cytotoxicity in dopaminergic cells, and pretreatment of the N27 cell with BM provided a cytoprotective response by modulation of oxidative stress and apoptosis (Shinomol et al ., ). Similarly, the beneficial outcomes of BM against apoptosis‐mediated toxicity caused due to paraquat/diquat have been studied (Singh et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Besides its role in memory enhancement, BM acts as a natural antioxidant and modulates oxidative stress induced by different toxic, environmental pollutant and chemical carcinogens. For example, BM found to prevent mitochondrial oxidative stress and dysfunctions induced by 3‐nitropropionic acid through modulation of superoxide dismutase, glutathione peroxidase, glutathione reductase and thioredoxin reductase in mice (Shinomol and Bharath, ). Similarly, BM has shown to prevent the effect of toxic pollutant including nitrobenzene and decabromodiphenylether from liver damage in rat and postnatal oxidative stress in the neonate and young female mice respectively (Verma et al ., ).…”
Section: Introductionmentioning
confidence: 99%